The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1063/1.3037023
|View full text |Cite
|
Sign up to set email alerts
|

IR/UV spectroscopy on jet cooled 3-hydroxyflavone (H2O)n (n=1,2) clusters along proton transfer coordinates in the electronic ground and excited states

Abstract: The structure and reactivity of isolated 3-hydroxyflavone (3-HF) aggregates with one and two water molecules has been investigated by applying combined infrared/ultraviolet (IR/UV) spectroscopy in a supersonic jet both for the electronic ground and excited states. In combination with density functional theory (DFT) calculations, the IR spectra of the S(0) states recorded from the upper fingerprint region to the OH stretching vibrations are assigned to the most stable isomers of the clusters. For the first elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…These experimentally obtained vibrational transitions fit excellently to the calculated frequencies of xanthone in the T 1 state (DFT/B3LYP/TZVP, scaled by 0.99, [9,10,49] Figure 4 b). The transitions can be assigned to combined CC stretching (ring deformation vibrations) and CÀH bending modes.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…These experimentally obtained vibrational transitions fit excellently to the calculated frequencies of xanthone in the T 1 state (DFT/B3LYP/TZVP, scaled by 0.99, [9,10,49] Figure 4 b). The transitions can be assigned to combined CC stretching (ring deformation vibrations) and CÀH bending modes.…”
supporting
confidence: 56%
“…To investigate structures of the electronic ground state, the IR photon arrives prior to an UV laser photon that excites the molecule to an energetically higher singlet state. [1][2][3][4][5] With variants of this technique, that is, by firing the IR laser after the first UV laser, the IR spectrum of electronically excited singlet states can also be recorded, [6][7][8][9][10] for example, as a depletion of the R2PI signal. Recently we have also shown that combined nanosecond UV/IR/UV spectroscopy in molecular beam experiments in combination with ab initio calculations yield structural information on isolated molecules and clusters in the electronically excited state subsequent to a proton transfer reaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…IR spectroscopy of excited states has been conducted on several biologically relevant systems [18,[216][217][218], as well as very recently on peptides [200], in order to provide a structural characterisation of the excited state. A first approach to record such spectra involves the use of a two-laser UV/IR detection scheme [18,216,217].…”
Section: Ir Spectroscopy Of Excited Statesmentioning
confidence: 99%